A Conceptual Model for Virtual Queuing System to Support Social Distancing - Gary Chia Wee, Kho; Bui Lin, Wee (IEEE, 2021)
In the early December 2019, Coronavirus Disease 2019 (COVID-19) epidemic outbreak emerged from Wuhan City, Hubei Province, China and spread rapidly to the rest of the world. Globally, IT Professionals were forced to adapt and innovate rapidly in response to the pandemic and have devised a variety of IT solutions to ease peoples’ transitions into the new normal. There are 4 major categories of IT-based COVID-19 solutions, namely contact tracing, quarantine management,symptom monitoring and information provision. However, most of these applications only focus on contact tracing as opposed to preventing the spread of the virus through the enforcement of social distancing. This paper presents a conceptual model for virtual queuing system, MyQueue which allows its users to enter virtual queues by scanning unique QR codes of various premises. It introduces proper process flows and approaches to eliminate waiting in a crowded queue and help support social distancing efforts to reduce the spread of COVID-19.